2012
DOI: 10.1123/jsep.34.2.159
|View full text |Cite
|
Sign up to set email alerts
|

Perfectionistic Profiles Among Elite Athletes and Differences in Their Motivational Orientations

Abstract: Although there is an emerging body of research that has examined perfectionistic clusters in the general population, few studies have explored such profiles in athlete samples. The purposes of this research were to explore perfectionistic profiles within a sample of elite athletes and the differences between them on key motivational variables. A sample of 423 elite athletes (179 males, 244 females) aged between 14 and 66 years (M = 25.64; SD = 8.57) from a variety of team (e.g., rowing, hockey, baseball, rugby… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
39
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(52 citation statements)
references
References 68 publications
8
39
0
2
Order By: Relevance
“…At the elite level, Gaudreau and Antl (2008) identified three categories of athletes: adaptive perfectionists; maladaptive perfectionists; and, non-perfectionists. Adaptive perfectionists score higher on mastery approach goals and lower on fear of failure than others (Gucciardi, Mahoney, Jalleh, Donovan, & Parkes, 2012). These findings suggest that perfectionism and motivation are linked, with motivation being an outcome and/or occupying a mediating role with another variable.…”
Section: Perfectionismmentioning
confidence: 96%
“…At the elite level, Gaudreau and Antl (2008) identified three categories of athletes: adaptive perfectionists; maladaptive perfectionists; and, non-perfectionists. Adaptive perfectionists score higher on mastery approach goals and lower on fear of failure than others (Gucciardi, Mahoney, Jalleh, Donovan, & Parkes, 2012). These findings suggest that perfectionism and motivation are linked, with motivation being an outcome and/or occupying a mediating role with another variable.…”
Section: Perfectionismmentioning
confidence: 96%
“…The motivational mechanisms of the basic psychological needs might over time underpin why some elite junior performers survive and thrive, despite adversity, and why others experience ill‐being and diminished functioning . Both personal and contextual factors are found to influence the motivational functioning of elite junior performers . Yet, few studies based on self‐determination theory (SDT) have investigated personal factors, even though they are likely to influence the perception of and reaction to environmental requests and demands, thereby influencing the satisfaction or frustration of the three basic psychological needs .…”
Section: Introductionmentioning
confidence: 99%
“…Perfectionism may be one personal factor associated with psychological need frustration. Perfectionism is viewed as a multidimensional personality trait or disposition, which is likely to influence motivational functioning in unique ways . Moreover, it is claimed to be paradoxical, energizes a strong motivational force (ie, dedication, effort, and persistence), yet, might also nurture debilitative patterns of cognition, emotion, and behavior .…”
Section: Introductionmentioning
confidence: 99%
“…In this context, studies have shown perfectionism traits as an antecedent of motivation in sport 2 . However, there is no consensus in literature on the potential association between adaptive and maladaptive perfectionism in sport performance 3,4 , especially regarding motivation in soccer players.…”
Section: Introductionmentioning
confidence: 99%
“…An interesting theoretical approach to investigate such associations is the Self-Determination Theory \ SDT 5 , which has shown evidence of complex relationships within sports psychology 6,7 . Specifically, studies in the field of sports science have shown the relationship between perfectionism and self-determined motivation 2,4 . However, our literature review points out this study as the first to address the prediction relationship between perfectionist orientations and motivation in soccer players.…”
Section: Introductionmentioning
confidence: 99%